2019
DOI: 10.1111/ger.12392
|View full text |Cite
|
Sign up to set email alerts
|

Access and barriers to oral health care for dependent elderly people living in rest homes

Abstract: Aim To report New Zealand rest home (rest home is the New Zealand term for residential aged care facilities where dependent, institutionalised, elderly people reside.) managers’ opinions on access and barriers to oral health care for rest home residents. Methods An exploratory study using qualitative descriptive methods. Eleven rest home managers in a region of New Zealand were interviewed about admission assessments for new residents, oral health care, availability of dental facilities, staff training in oral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 14 publications
1
23
0
2
Order By: Relevance
“…Apart from the physical and cognitive impairments that tend to limit the access to dental care of dependent elderly people, other barriers, such as dental treatment charges, could also restrict elderly people from seeking dental care. Studies worldwide have reported that finances could act as barrier to the elderly, with severity varying as a function of the socio‐economic status of the patients among other factors 24‐27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the physical and cognitive impairments that tend to limit the access to dental care of dependent elderly people, other barriers, such as dental treatment charges, could also restrict elderly people from seeking dental care. Studies worldwide have reported that finances could act as barrier to the elderly, with severity varying as a function of the socio‐economic status of the patients among other factors 24‐27 …”
Section: Discussionmentioning
confidence: 99%
“…Studies worldwide have reported that finances could act as barrier to the elderly, with severity varying as a function of the socio-economic status of the patients among other factors. [24][25][26][27] A study conducted on mobile services set up by different organisations in the United States of America, reported the use of a variable configuration of models, 9 similar to the university services in Switzerland. Fixed dental clinics have the clear advantage of having all the dental equipment available and the possibility to deliver all types of dental care.…”
Section: Discussionmentioning
confidence: 99%
“…Several national studies have reported on the oral health of older people in aged residential care and their caregivers’ knowledge of oral care 12‐15 . To date, only one has included detailed data on the oral health of home‐based older people who receive living support.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, poor oral health status among elders may also lead to other health complications that can impede activities in their daily life. It has been reported that oral health care often takes second place to chronic and life‐threatening diseases in many aspects among elders 5…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that oral health care often takes second place to chronic and life-threatening diseases in many aspects among elders. 5 In general, elders have poorer oral health than younger people.…”
Section: Introductionmentioning
confidence: 99%